2019
DOI: 10.1007/s13595-019-0887-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of black poplar (Populus nigra L.) seed storability

Abstract: & Key message Adequate storability of black poplar (Populus nigra L.) seeds at temperatures below 0°C was associated with preservation of proteins of energy and carbohydrate metabolism, protein turnover, and proteins maintaining longterm stability of dehydrated tissue. & Context Understanding seed storability is a key factor for effective seed preservation and conservation. Black poplar is an endangered tree species and its seed loses rapidly viability during storage. & Aims The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…As the weight of a seed is linked to the energy reserves available as an embryo develops into a seedling, it seems reasonable to assume that a difference in mass should lead to a difference in vigour, and that seeds' sizes should correlate with their survival rates. However, the relationships are highly taxon-dependent, as demonstrated by previously reported positive and negative correlations between these parameters (González-Rodríguez et al, 2012;Rajjou et al, 2012;Zhang et al, 2015;Ghaffaripour et al, 2017;Wang et al, 2018). We observed no significant differences in three consecutive years in seedlings' germination rates, between either families or populations.…”
Section: Consequences Of Seed Size For Germination and Growth Of Juve...mentioning
confidence: 89%
See 1 more Smart Citation
“…As the weight of a seed is linked to the energy reserves available as an embryo develops into a seedling, it seems reasonable to assume that a difference in mass should lead to a difference in vigour, and that seeds' sizes should correlate with their survival rates. However, the relationships are highly taxon-dependent, as demonstrated by previously reported positive and negative correlations between these parameters (González-Rodríguez et al, 2012;Rajjou et al, 2012;Zhang et al, 2015;Ghaffaripour et al, 2017;Wang et al, 2018). We observed no significant differences in three consecutive years in seedlings' germination rates, between either families or populations.…”
Section: Consequences Of Seed Size For Germination and Growth Of Juve...mentioning
confidence: 89%
“…seeds has negative consequences for breeding and genetic conservation programs (Muller et al, 1982;Stanton & Villar, 1996). Hence, attempts have been recently made to address these problems and identify optimum protocols for ex situ seed conservation (Suszka et al, 2014;Michalak et al, 2015;Pawłowski et al, 2019). Following demonstrations that they can be stored up to several years in specific conditions, seeds of the species have been re-classified as intermediate between orthodox seeds, which can withstand dehydration to water contents as low as 50 mg.g -1 (Roberts, 1973), and recalcitrant seeds (Bonner, 2008;Suszka et al, 2014;Michalak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bonner (2008) and Pritchard & Nadarajan (2008) mentions that seeds can be kept viable for several years, when stored at sub-zero temperatures and in a dry atmosphere. For future research, we suggest to include treatments at temperatures below 0 °C and cryopreservation for more promising ex situ seed conservation of these species (Suszka et al 2014), as it has been shown that these techniques could obtain favorable results in longevity and maintain viability for longer periods (Pawłowski et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental variability (seasonality) is crucial to explaining the existence or absence of dormancy and evolutionary transitions between these states [ 46 ]. In addition to the genetic background of this adaptation, environmental factors can shape the depth of dormancy and seed germination [ 8 , 47 ]. Models developed for climate change scenarios show that many species would face a significant decrease in suitable habitat area [ 48 ], also because of disturbances in the reproduction process ( Figure 1 ).…”
Section: Adaptations Of Seed Germination To the Changing Environmementioning
confidence: 99%